Greater coronary lipid core plaque assessed by near-infrared spectroscopy intravascular ultrasound in patients with elevated xanthine oxidoreductase: a mechanistic insight. (25th November 2020) - Saito, Y; Mori, N; Saito, K; Matsuoka, T; Tateishi, K; Kitahara, H; Fujimoto, Y; Kobayashi, Y
Abstract: Background: Elevated serum uric acid level was reportedly associated with greater coronary lipid plaque. Xanthine oxidoreductase (XOR) is a rate-limiting enzyme in purine metabolism and believed to play important roles in coronary atherosclerosis. However, the relation of XOR to coronary lipid plaque and its mechanism are unclear. Purpose: The aim of this study was to assess the impact of XOR on coronary lipid plaque and the associated factors with XOR in coronary artery disease (CAD). Methods: Patients with stable CAD undergoing elective percutaneous coronary intervention under near-infrared spectroscopy intravascular ultrasound (NIRS-IVUS) guidance were prospectively enrolled. They were divided into three groups according to serum XOR activities; low, normal, and high. Coronary lipid core plaques in non-target vessels were evaluated by NIRS-IVUS with lipid core burden index (LCBI) and a maximum LCBI in 4 mm (maxLCBI4mm). Systemic endothelial function and inflammation were assessed with reactive hyperemia index (RHI) and high-sensitivity C-reactive protein, neutrophil-to-lymphocyte ratio, and platelet-to-lymphocyte ratio. Results: Of 68 patients, 26, 31, and 11 were classified as low, normal, and high XOR activity groups. LCBI (474.4±171.6 vs. 347.4±181.6 vs. 294.0±155.9, p=0.04) and maxLCBI4mm (102.1±56.5 vs. 65.6±48.5 vs. 55.6±37.8, p=0.04) were significantly higher in high XOR group than in normal and low XOR groups. Although RHI was significantly correlated with body mass index, diabetes, current smoking, and high-density lipoprotein cholesterol, no relation was found between XOR activity and RHI (Figure). There were also no relations between XOR activity and high-sensitivity C-reactive protein, neutrophil-to-lymphocyte ratio, or platelet-to-lymphocyte ratio (Figure). Conclusion: Elevated XOR activity was associated with greater coronary lipid plaque in patients with stable CAD, without significant relations to systemic endothelial function and inflammation. Funding Acknowledgement: Type of funding source: None